BIOECOLOGICAL FEATURES AND PROPAGATION METHODS OF SELECTED Lonicera L. SPECIES USING INNOVATIVE SUBSTRATES (American Journal of Pedagogical and Educational Research, 2026)
This study examines the bioecological traits of several species within the genus Lonicera L., along with their propagation techniques in different substrate conditions and the effectiveness of root formation. The research focuses on small-leaved, Tatar, and glossy-leaved honeysuckle species, evaluating their morphophysiological responses across various growing environments. The findings indicate that substrates based on coconut peat, as well as peat mixtures, demonstrate superior performance in terms of rooting success and overall plant development.